41. CLINICAL CHARACTERISTICS OF SLEEP DISORDERS IN ELDERLY PATIENTS WITH HYPERTENSION IN THE SUBURBAN AREAS OF HANOI (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of sleep disorders in elderly hypertensive patients in the suburbs of Hanoi in 2024-2025.Objects and methods: Descriptive, cross-sectional study, describing the current status of sleep disorders in 385 elderly hypertensive patients receiving outpatient treatment at 3 medical stations of Phuc Lam, Cao Thanh, Quang Bi communes in the suburbs of Hanoi from September 2024 to March 2025.Results: The mean age of the study subjects was 71.0 ± 6.8 years; 59% of the patients were female. The rate of patients with sleep disorders is 57.1%, of which 91.8% are insomniacs. In patients with sleep disorders, the time of insomnia in patients over 3 months accounts for 72.3%, the rate of insomnia at the beginning of sleep is 35.5%, the majority of patients have a time to fall asleep over 30 minutes and wake up in the middle of the night from 1-4 times/night; 38.1% of subjects had a frequency of waking up too early in the morning ≥ 3 times/week; 50.5% of patients have moderate sleep disorders.Conclusion: Sleep disorders are very common in elderly hypertensive patients, of which insomnia is the most common type of sleep disorder, characterized by difficulty falling asleep, difficulty maintaining sleep, short sleep duration, and poor sleep quality.
Keywords: Hypertension, sleep disorders, elderly patients.